COMMUNITY EMPOWERMENT STRATEGIES THROUGH MEDIATION TECHNICAL GUIDANCE IN LAND DISPUTE RESOLUTION - Rafie, Patih Ahmad; Merta, M. Martindo; Junaidi, Junaidi (JOURNAL OF SUSTAINABLE COMMUNITY SERVICE, 2023)
The purpose of this research is to evaluate the effectiveness of mediation technical guidance in land dispute resolution in Sirah Pulau Padang Sub-district, Ogan Komering Ilir Regency, South Sumatra Province. The research method used was technical guidance and interactive discussions, as well as mediation simulations involving participants from various backgrounds, such as Village Heads, Heads of Neighborhood Associations, Community Leaders, Babinsa, and community members. Data were collected through interviews, questionnaires, and observations. The evaluation results showed that the mediation technical guidance program was effective in improving participants' understanding of land dispute resolution through mediation and sparked enthusiasm in disseminating information about land dispute resolution through mediation. In addition, the mediation simulation also helped participants in identifying problems in conflicts from various perspectives and increased participants' experience in finding alternative agreements between the parties. Therefore, mediation technical guidance can be effective in empowering communities to resolve land disputes and increase legal certainty in the land context.